PHYSIOLOGICAL CHANGES DURING STORAGE OF POTATO PRODUCTS (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
This article describes the physiological changes that occur during the storage of potato products, the effect of different containers on the chemical and quantitative composition of the product and the losses caused by them, the processes that take place in the tubers, and their analysis.